An evaluation of the effects of metal complexes on lung cancer cell lines - Mangena, Zanele (University of the Witwatersrand, Johannesburg, 2024)
Lung cancer remains a predominant global health concern, accounting for approximately 18% of cancer-related deaths. In South Africa, it imposes a significant burden due to high rates of late-stage diagnoses, resulting in compromised survival outcomes. Despite available targeted therapies, treatment efficacy is hindered by drug resistance and severe side effects, highlighting the need for alternative agents. This study aimed to investigate a series of complexes in an in vitro setting to assess their potential as alternative agents for lung cancer therapy. This study evaluated 20 compounds, encompassing novel epidermal growth factor receptor kinase inhibitors, AD and OM copper complexes, and copper imidazo[1,2-a]pyridines in vitro. Their cytotoxicity against A549 lung cancer cells was determined by the MTT assay, and the most potent compounds were chosen for further investigation. The mode of cell death for these compounds was assessed through cell morphology, Annexin-V, caspase-3/7, mitochondrial membrane potential, and caspase-8 assays. The capacity of the active compounds to induce reactive oxygen species was measured through the CellROX™ Deep Red assay kit. Immunohistochemistry techniques were employed to analyze the expression and distribution of p21 and p53. Furthermore, changes in the expression levels of apoptosis-related proteins post-treatment with the most effective compound were assessed using the Proteome Profiler Human Apoptosis Array kit. Four copper-imidazo[1,2-a]pyridines, namely JD35, JD46, JD47, and JD88, were the most active, with IC50 values in A549 cells between 1.67 μM and 3.37 μM. These compounds induced apoptotic cell death, characterized by chromatin condensation, fragmented nuclei, Annexin-V binding, and activation of caspase-3/7. They also caused a decline in mitochondrial membrane potential, indicating activation of the intrinsic apoptotic pathway, while also inducing late caspase-8 activation. Furthermore, these compounds enhanced reactive oxygen species and upregulated nuclear p21 and p53 expression, suggesting DNA damage leading to apoptosis initiation. Analysis of apoptotic proteome array data showed that JD88 treatment significantly upregulated the wild-type tumour suppressor protein, p53 in A549 cells while significantly downregulating anti-apoptotic proteins such as Bcl-2, Bcl-xL, XIAP, cIAP-2, survivin, and heat shock proteins (HSP27, HSP60, and HSP70). These findings suggest a reduced threshold for apoptosis and a potential promotion of apoptosis, possibly through p53 activation. Copper-imidazo[1,2-a]pyridines have demonstrated effectiveness in inducing apoptotic cell death in A549 cells, impacting both intrinsic and extrinsic apoptotic pathways and influencing critical proteins for cellular survival and apoptosis. This study contributes to a better comprehension of apoptotic mechanisms in A549 cells, stimulating inquiries into the activation of extrinsic apoptotic pathways especially by copper complexes. These findings support further pre-clinical evaluations of copper-imidazo[1,2-a]pyridines, including efficacy assessments in lung cancer animal models, toxicity studies, and determination of pharmacokinetic properties
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg 2024
Keywords: Lung cancer; Lung cancer cell lines; UCTD; SDG-3: Good health and well-being